Indoor air quality guide : best practices for design, construction, and commissioning. (Online access with JISC subscription agreement: Knovel., 2009)
"Comprehensive, practical resource on design and construction for enhanced indoor air quality (IAQ) in commercial and institutional buildings. Useful for architects, engineers, building owners concerned with high-quality indoor environment. Focuses on today's major IAQ issues: moisture management, ventilation, filtration and air cleaning, and source control"--Provided by publisher.